Block, Joern, Karsten Kohn, Danny Miller y Katrin Ullrich. 2015 “Necessity entrepreneurship and competitive strategy”. Small Business Economics. New York, volumen 44, número 1, pp. 37-54. - Córdova, Miguel (2016)
No presenta resumen